Lions of the Skeleton Coast [videorecording (DVD)] - Dumezweni, Noma (PBS, 2024)
In this astonishing true story, lion researcher Dr Philip Stander is witness to the most unprecedented lion behaviour whilst following three orphaned Desert Lion cubs, as they navigate the harsh realities of survival in one of the world's most unforgiving environments, Namibia's deadly Skeleton Coast.